2014
DOI: 10.1038/srep05697
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine phosphorylase gene variant, platelet counts and survival in gastrointestinal cancer patients treated by fluoropyrimidines

Abstract: The predictive value of thymidine phosphorylase gene variants (TP, also called platelet-derived endothelial cell growth factor) and thrombocytosis were controversial and worthy of further study in gastrointestinal cancer (GIC) patients. We screened all of the common missense single nucleotide polymorphisms (MAF ≥ 0.1) in fluoropyrimidines (FU) pathway genes (including TP, TS, ENOSF1 and DPD). Three of them were selected and genotyped using Sequenom MassARRAY in 141 GIC patients. TP expression was assessed by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Additionally, another study initiated by Liu et al investigated the relevance of TYMP genetic variation to the survival of gastrointestinal cancer patients treated with fluoropyrimidines. 15 A total of 141 metastatic gastrointestinal cancer patients who received 5-FU-based first-line chemotherapy were included and the results suggested that A allele gene carriers were associated with higher TYMP gene expression, which was consistent with the mRNA expression results in our study. However, they failed to identify the positive association of the polymorphism with OS mainly own to the relatively limited sample size.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, another study initiated by Liu et al investigated the relevance of TYMP genetic variation to the survival of gastrointestinal cancer patients treated with fluoropyrimidines. 15 A total of 141 metastatic gastrointestinal cancer patients who received 5-FU-based first-line chemotherapy were included and the results suggested that A allele gene carriers were associated with higher TYMP gene expression, which was consistent with the mRNA expression results in our study. However, they failed to identify the positive association of the polymorphism with OS mainly own to the relatively limited sample size.…”
Section: Discussionsupporting
confidence: 88%
“…Besides, another study initiated by Huang et al investigated the clinical significance of TYMP gene polymorphism among patients with advanced gastrointestinal tumors. 15 Conclusion suggested that the expression level of TYMP gene was higher among patients with T allele in the advanced gastrointestinal tumors. Nevertheless, the relevance of TYMP polymorphism to the prognosis of patients with CRC who received capecitabine-based adjuvant chemotherapy after surgical resection remained unknown.…”
Section: Introductionmentioning
confidence: 96%
“…This may be due to that peptide-associated epitope, which can be influenced by polymorphisms [115], is involved in an antigenic recognition. Patients carrying the T allele of TYMP, rs11479, are likely to show a high level of TYMP expression in tumor tissue [116], suggesting this may be a specific target for TYMP targeted antitumor immunotherapy.…”
Section: The Role Of Tymp In the Development Of Chronic Diseasesmentioning
confidence: 99%
“…Although more than 160 polymorphisms in DPYD gene have been identified to date, data derived from Chinese cancer patients is very limited [ 19 , 20 ]. In the present study, we detected 5 polymorphisms including c.74A>G, c.85T>C, c.1627A>G, c.1896T>C and c.2194G>A in breast cancer patients of China north area; and the genotype frequencies of these polymorphisms in our study were similar to previous research [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%